The Effect Of Tax Audit, Tax Collection And Tax Socialization On Revenue Tax Personnel At The Service Office Tax Primary Denpasar East - Ni Nyoman Ayu WIDIGINANTRI; AA Ayu Erna TRISNADEWI; I Gusti Ayu Athina WULANDARI (Indonesia Strategic Sustainability, 2022)
The purpose of this study was to determine the effect of tax audits, tax collection and tax socialization on individual tax receipts at the East Denpasar Pratama Tax Service Office. This study uses primary data in the form of a questionnaire, the data is obtained directly from the source through respondents' answers at the East Denpasar Pratama Tax Service Office. The population in this study includes individual taxpayers who are registered at the East Denpasar Pratama Tax Service Office, amounting to 129,542 people. The research sample amounted to 100 respondents with a sampling technique that is purposive sampling method which has the following criteria: 1) Individual taxpayers who already have a Taxpayer Identification Number (NPWP) as their identity. 2) Individual taxpayers who are registered and active in the East Denpasar KPP Pratama office and have carried out tax payment activities. This study uses three independent variables, namely tax audit, tax collection, and tax socialization. Furthermore, individual tax receipts are used as the dependent variable. This research uses multiple linear regression analysis technique with SPSS software. The results of this study indicate that the tax audit has a positive and significant effect on individual tax revenues. Tax collection has a positive and significant effect on individual tax receipts. Tax socialization has a positive and significant effect on individual tax revenues.